Pengaruh Pembelajaran Daring terhadap Pemahaman Materi Mahasiswa - Palma Juanta; Sola Gratia Hutasoit; Yusup Aritonang; Tan Lisaifung (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effect of online learning on students' material comprehension at Universitas Prima Indonesia. A quantitative approach with a survey design was employed, involving 60 respondents selected through random sampling. Data were collected using a Likert-scale questionnaire (15 items) and analyzed using descriptive statistics and the Spearman's Rank correlation test due to non-normal data distribution (Sig. < 0.05). The results showed that both online learning implementation (mean=17.30) and students' comprehension (mean=11.91) were in the "fair" category. The Spearman's Rho correlation coefficient was 0.844 (Sig. = 0.000 < 0.05), indicating a very strong and significant positive relationship. Thus, the better the implementation of online learning, the higher the students' comprehension of the material. This study concludes that online learning significantly influences students' comprehension, although it requires support from stable internet connectivity and interactive teaching methods.